Ānāpāna: Neuro-engineering of Mindfulness - Ferrin Bolaños, Carlos Diego; Correa Agudelo, Esteban Mauricio; Hernandez Camacho, Andres Mauricio; Gómez, Juan Diego (Scientia et Technica, 2016)
Meditation benefits have been widely supported by many research works. It is considered a natural way of reducing stress, depression, and other anxiety disorders. However, meditation process is a breathe pursuing task that requires long time training to avoid the so-called mind wandering. In this work, we propose a neural-feedback system that detects when mind wanders and generates an audible signal, this way patient’s attention is recovered back again. Finally, we support our approach by testing the system on novice and advanced meditators.